Clinical Risk Index for Babies (CRIB-II) Scoring System in Prediction of Mortality Risk in Preterm Neonates in the First 24 Hour - Firuzeh Faridpour; Azam Shirinabadi Farahani; Maryam Rassouli; Mamak Shariat; Malihe Nasiri; Mina Ashrafzadeh (Mashhad University of Medical Sciences, 2020)
Background: The scoring systems evaluate neonatal outcomes based on perinatal factors in the Neonatal Intense Course Unit (NICU). Aim: This study aimed to predict mortality risk in preterm neonates for the first time, using the Clinical Risk Index for Babies (CRIB II). Method: This cross-sectional, descriptive-analytical, longitudinal study was conducted on 344 preterm neonates with the gestational age of 23-32 weeks and birth weight of 500-1500 g in a referral center in Tehran, Iran, from winter 2016 to spring 2017. Some neonatal variables were completed within the first 12 h of life, and the final scores were calculated based on CRIB II. Then, the correlation of these variables with mortality outcome was evaluated using logistic regression. Sensitivity, specificity, and positive and negative values were also calculated via SPSS software (version 23). Results: According to the results, 253 (73.57%) neonates, including 122 girls (48%), survived in the first 24 h after birth. The total CRIB II score in the surviving neonates was 6.1±2.6. The area under the receiver operating characteristic curve was estimated at 0.84 with the cut-off point of 8.5. In addition, the sensitivity, specificity, positive predictive value, and negative predictive value of the CRIB II system were obtained as 75%, 78%, 55%, and 89.5%, respectively. The results revealed a significant correlation between the CRIB II score and mortality outcome. In this regard, an increase in the CRIB score coincided with a 0.67 increase in the risk of death (OR=1.671, P<0.001). Implications for Practice: Based on the findings of the present study,CRIB II can be concluded to be an appropriate scoring system. Consequently, the result of this tool can be used for routine investigations.